ВИДІЛЕННЯ ВОДНЮ НА ТИТАНОВОМУ ЕЛЕКТРОДІ З РОЗЧИНУ СІРЧАНОЇ КИСЛОТИ - Kozin, Valentin; Bliznyuk, Antonina (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2022)
Thanks to the unique combination of physicochemical properties, metal hydrides (MH) are widely used in various fields of science and technology. High thermal, chemical and radiation resistance MH allows it to be used in nuclear industry as a material for nuclear reactors, chemical engineering, metallurgy for the production and refining of metals, for the production of devices operating at elevated temperatures and in adverse conditions. Unique properties MH are widely used in hydrogen energy as hydrogen storage, in rechargeable batteries. Analysis of literature data has shown that most studies are devoted to the practical use of the unique MH ability of reversibly absorbs a large amount of hydrogen. However, the electrochemical characteristics of the electrode processes of metal hydride systems were practically not investigated. The aim of this work is to study the processes that take place on the titanium electrode in sulfuric acid solutions, and the composition of titanium compounds that are formed. The paper presents the results of studies of the hydride formation reactions occurring on a polarized titanium cathode in aqueous solution 2 N sulfuric acid. The study was carried out using the following methods: the cyclic voltammetry and the method of x-ray phase analysis of the composition of the surface. It has been found that the reduction of hydrogen at the titanium cathode from a solution of sulfuric acid is accompanied by the formation of hydrides, which causes an increase in the overvoltage of hydrogen evolution and high values of the angular coefficients of the Tafel dependence. The kinetic parameters of this process have been calculated: the transfer coefficients α, theoretical and experimental angular coefficients btheor and bexp , exchange currents ie, the dependence of the hydrogen overvoltage from temperature. It has been found that exchange current density of hydrogen evolution reaction in this system is close by value to the current exchange of hydrogen evolution at the noble metals Pd, Pt, Rh, Ir and are (2,70∙÷0,8)∙10-3А·sm-2 in the temperature range 298 ÷ 343 K. The value of activation energy of 19,83 kJ mol-1 indicates the diffusion control of this process.